VD_FINDINFO HC / 2010 / 720 vom 29. November 2010 - VD Tribunal cantonal (2010)
MODÉRATION, HONORAIRES, AVOCAT, DÉCOMPTESENS GÉNÉRAL, RÉDUCTIONEN GÉNÉRAL | 12 let. i LLCA, 45 al. 1 LPAv, 48 LPAv, 50 al. 1 LPAv, 51 LPAv